2017
DOI: 10.1155/2017/5437830
|View full text |Cite
|
Sign up to set email alerts
|

Osteopathic Manipulative Treatment Limits Chronic Constipation in a Child with Pitt-Hopkins Syndrome

Abstract: Pitt-Hopkins Syndrome (PTHS) is a rare genetic disorder caused by insufficient expression of the TCF4 gene. Children with PTHS typically present with gastrointestinal disorders and early severe chronic constipation is frequently found (75%). Here we describe the case of a PTHS male 10-year-old patient with chronic constipation in whom Osteopathic Manipulative Treatment (OMT) resulted in improved bowel functions, as assessed by the diary, the QPGS-Form A Section C questionnaire, and the Paediatric Bristol Stool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Considering the altered gut motility, permanent therapy with osmotic laxatives, stool softeners, and a diet rich in fibers may be taken into consideration. Recently, Aquino et al reported the case of a 10-year-old child affected by severe constipation and treated with osteopathic manipulative sessions [ 16 ]. This type of approach showed good results in terms of evacuation frequency and reduction of enema administration but further studies with a larger cohort are needed to define its actual effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the altered gut motility, permanent therapy with osmotic laxatives, stool softeners, and a diet rich in fibers may be taken into consideration. Recently, Aquino et al reported the case of a 10-year-old child affected by severe constipation and treated with osteopathic manipulative sessions [ 16 ]. This type of approach showed good results in terms of evacuation frequency and reduction of enema administration but further studies with a larger cohort are needed to define its actual effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…These elements favor the onset of extremely prolonged intestinal transit and, decreased colon motility that result in frequent manifestations of abdominal distension, constipation accompanied by symptoms such as bloating, pain and abdominal constipation [ 38 ]. The starting hypothesis of the study was based on the assumption that OMT may influence the central nervous system [ 20 , 21 ], autonomic nervous system [ 14 ], haemodynamic system [ 14 ] and visceral motility [ 23 ] as reported in previous clinical studies [ 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, pelvis and head also were treated for a long time. In light of the primary outcome measure results and the OMT beneficial effects on QoL, the combination of these data suggests that myofascial and visceral manipulation techniques, applied to the above regions, may allow visceral vascularization and can restore the physiological elasticity and mobility of the viscera [ 25 ] with a consequent reduction in the bowel-related symptoms. Future studies could be aimed at confirming these data and also could compare the effects of different techniques on OMT effectiveness in patients with NBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OMT has shown preliminary efficacy in adults with functional constipation [11], in reducing gastrointestinal symptoms caused by adjuvant chemotherapy [12] and in patients with distal intestinal obstructive syndrome [13]. However, OMT effects have been described only in 1 case of a child with chronic constipation related to Pitt-Hopkins syndrome, showing an increment in defaecation frequency and better Bristol Stool Chart scores during the treatment period [14].…”
Section: Discussionmentioning
confidence: 99%